Sistem Monitoring dan Pengendalian Suhu Otomatis Berbasis IoT Untuk Greenhouse Dengan Algoritma Fuzzy Logic - Imran, Faizur Rahman; Rahana, Gunawan; Mahda, Fajri Hidayat; Sari, Dessy Ana Laila (CV. Sekawan Siji, 2024)
In facing the challenges of climate change that affect the agricultural sector, automatic monitoring and control systems are important solutions to ensure optimal conditions for plant growth. This study develops an Internet of Things (IoT)-based system and fuzzy logic algorithms to automatically control temperature and humidity in a greenhouse. This system uses a DHT22 sensor to measure temperature and humidity, ESP32 as a microcontroller, and actuators such as fans and heaters to adjust environmental conditions. The fuzzy logic algorithm enables adaptive decision making based on real-time data collected. The research methodology adopts the ADDIE development model which includes analysis, design, development, implementation, and evaluation. The implementation results show that the system is able to improve the efficiency of greenhouse environmental management, maintain the stability of temperature and humidity parameters, and increase plant productivity. This technology is a step forward in supporting the sustainability of modern agriculture.